The broom, the simpathy and the sword: images of brazilian democracy in the fifties (Tempo e Argumento, 2012)
This article studies the representation of Brazilian democracy in the fifties, through the analysis of the photojournalism in O Cruzeiro magazine. Based on articles on three politicians, frequently mentioned in the magazine during the time period studied – Jânio Quadros, Juscelino Kubitscheck and Henrique Teixeira Loft – we identified values promoted and disseminated by the magazine related to politics and politicians in this period of time, aiming to build a specific image of the Brazilian democracy in the fifties. The analysis considered the specificity of the sources, that is, articles with visual predominance over writing.
Keywords: democracy; images; representation; photojournalism; O Cruzeiro magazine